Adsorptions of phenol molecules by graphene-based nanostructures, modified with nitrogen and bromine, from petroleum wastewater using molecular dynamics simulation - Said, Hanaa Mohamed; D'Orazio, Annunziata; Sajadi, S. Mohammad; İnç, Mustafa (Elsevier Sci Ltd, 2023)
Today, industrial wastewater treatment has attracted the attention of many governments and environmental experts. Basically, the pollution of these wastewaters is due to the presence of organic pollutants such as dyes, halogenated hydrocarbons, phenolic compounds, etc. Meanwhile, phenol is widely used in oil, petrochemical, coal production, and pharmaceutical industries. Several methods such as surface adsorption are used to remove phenol from water. In this work, the adsorption of phenol molecules by carbon nanostructures and carbon nanostructures modified with nitrogen and bromine has been investigated using Molecular Dynamics simulation. According to the obtained results, BCN-graphene has been introduced as the best nanostructure for the removal of phenol molecules from the aqueous environment, having the highest adsorption energy and greater adsorption stability. This work paves the way for the development of the use of bromine nitride structures in the treatment of petroleum wastewater.
Keywords: Adsorption of phenol molecules; Carbon nanostructures; Molecular Dynamic; Graphene